Addiction Medicine Practice-Based Research Network (AMNet): Assessment Tools and Quality Measures - Clarke DE; Ibrahim A; Doty B; Patel S; Gibson D; Pagano A; Thompson L; Goldstein AB; Vocci F; Schwartz RP (Dove Medical Press, 2021)
Diana E Clarke,1,2 Adila Ibrahim,3 Benjamin Doty,1 Sejal Patel,1 Debbie Gibson,1 Anna Pagano,4 Laura Thompson,1 Amy B Goldstein,5 Frank Vocci,3 Robert P Schwartz3 1Division of Research, American Psychiatric Association, Washington, DC, USA; 2Department of Mental Health, Johns Hopkins Bloomberg School of Public Health, Baltimore, MD, USA; 3Social Research Center, Friends Research Institute, Baltimore, MD, USA; 4Quality and Science Department,American Society of Addiction Medicine, Rockville, MD, USA; 5Prevention Research Branch,National Institute on Drug Abuse, Bethesda, MD, USACorrespondence: Diana E ClarkeAmerican Psyshiatric Association, 800 Maine Avenue SW, Suite 900, Washington, DC, 20024, USATel +1 202-609-7120Email dclarke@psych.orgIntroduction: The need for innovative approaches to address the opioid epidemic in the United States is widely recognized. Many challenges exist to addressing this epidemic, including the obstacles outpatient substance use treatment practices face in implementing measurement-based care (MBC), quality measurement systems, and evidence-based treatments. Also, there are insufficient opportunities for clinicians in these settings to participate in research, resulting in diminished translation of research findings into community-based practice. To address these challenges, the Addiction Medicine Practice-Based Research Network (AMNet) was developed to facilitate the uptake of MBC in outpatient practices via implementation of patient-reported assessments and quality of care performance measures to improve patient outcomes. This network will offer clinicians in outpatient settings (not incuding opioid treatment programs [OTPs]) the opportunity to participate in future substance use disorder treatment research studies.Methods: A key step in the development of AMNet was the selection of substance use-specific assessment tools and quality of care performance measures for incorporation into the American Psychiatric Association's mental health patient registry, PsychPRO. A scoping review and multi-step consensus-based process were used to identify, review and select candidate assessment tools and quality of care performance measures for opioid use disorders (OUD) and substance use disorders (SUD).Results: Following a consensus-based methodology, 12 standardized assessment tools and 3 quality of care performance measures for OUD and SUD were selected to help facilitate the implementation of MBC and quality improvement for AMNet participants. These tools were further categorized as core and optional.Conclusion: By offering a collection of carefully vetted assessment tools and quality measures through PsychPRO, AMNet will help participating clinicians with the systematic uptake of MBC and delivery of evidence-based treatment for patients with SUD. Also, AMNet will act as a centralized repository of data collected from patients and clinicians in non-OTP outpatient addiction medicine practices and serve as a platform for opioid treatment research.Keywords: measurement-based care, addiction medicine, patient-reported outcome measures, quality measures, quality improvement